A the impact of leadership styles towards employee job satisfaction among employees in Jabatan Pelajaran Melaka / Haslinda Othman - Othman, Haslinda (Faculty of Business and Management, 2013)
The purpose of this study is to identify the current level of employee job satisfaction among government servant in JKR Melaka and to examine the relationship of transformational, transactional and laissez-faire leadership style on employee job satisfaction. Employees used as respondent are range from lower level employees to middle level employees. One hundred and eighty one employees will be chosen for this study. These employees were assessed using the Multifactor Leadership Questionnaire (MLQ) developed by Bass and Avolio (2009) to determine their leadership styles. Whereas the MSQ Questionnaire by University of Minnesota copyright 1967 and JSS Questionnaire by Paul E. Spector (2007) were used for dependent variable of employee job satisfaction. Finding of this study only implies at Jabatan Kerja Raya Melaka of government sector only. Five leadership styles will be used in this study including pay, work, promotion, co-workers and supervision. The [mdings are suitable for managing government organizations.